The Role of Counseling on the Utilization of Family Medicinal Plants as Traditional Herbal Remedies on the Knowledge Level of the Community in Datarajan Village - Diah Kartika Putri; Prasojo Pribadi; Vicko Suswidiantoro; Taufiki Miftausakina (Al Makki Health Informatics Journal, 2026)
The use of medicinal plants as traditional remedies offers synergistic effects, in which combinations of several plant species can enhance treatment effectiveness. Indonesia possesses the second-largest biodiversity in the world, with approximately 25,000–30,000 plant species, of which around 7,500 have been identified as having medicinal potential; however, only approximately 1,200 species are utilized as traditional medicines. This study aimed to determine the level of community knowledge and examine the effect of counseling on knowledge regarding the utilization of Tanaman Obat Keluarga (TOGA) as traditional herbal remedies. The study employed a quasi-experimental method with a non-equivalent control group design. The results showed that among 120 respondents in the intervention group, the majority demonstrated a good level of knowledge, with 71 respondents (59%) categorized as having good knowledge. The Mann–Whitney test results indicated a p-value of 0.000, demonstrating a significant difference between groups. This study concluded that community knowledge was categorized as good and that counseling had a significant effect on the knowledge level of the community in Datarajan Village, Ulu Belu District, Tanggamus Regency, regarding the utilization of Tanaman Obat Keluarga (TOGA) as traditional herbal remedies.